ONLINE TRAVEL AGENTS USE FOR SALES AND PROMOTION OF HOTEL IN KALIURANG YOGYAKARTA - Kristianto, Dwi Agus; Syamsu, Moch Nur; Sarwono, Aldi Wisnumurti (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2018)
Although traditional travel agents have played an important role as proxies enabling travelers to make connections with hotels, the emergence of the internet has changed the traditional relationship between hotels and travel agents. Instead of a traditional agent–principal relationship, online travel agents (OTAs) seem to act as more than just intermediaries and more as business partners or vendors. Scholars have previously observed troubled, if not hostile, relationships between hotels and OTAs. There has been a growing tendency for hotel and accommodation business worldwide to use online travel agents (OTAs) to promote and sell their rooms. This research discusses the advantages and disadvantages of the promotion and sales through OTAs for hotel business in Kaliurang a famous tourism destination object in Yogyakarta. The object of the research is the hotel manager, supervisors and staff who handle the hotel promotion and sales of their accommodation business. Hotel were located in Kaliurang chosen based on cluster proportional and the informants were chosen based on purposive sampling technique. The result shows that the disadvantages in using OTAs as promotion and sales tool are rising occupancy, direct payment, and as a tool in making hotel well known worldwide. The disadvantages are decrease net sales, over booking, negative comments could downgrade the hotels rank, and OTAs make hotels website got limited traffic. The motivation of hotel managements in using OTAs is highly motivated. The dominant factor of the perception included factors in self-perception of the target, factor in the self-perception, and factors perception of situation. This research suggests to the villa management to recruit special personnel for handling OTAs as well as to manage own websites to increase the net sales.